Da formação ludopiética à autopoiese do lazer: significados para a autoformação humanescente do profissional do lazer - Maia, Sonia Cristina Ferreira (2008)
The present study aimed to understand and interpret the connections between the training of graduate ludopoiética leisure and the process of autopoiesis of leisure. From the main objective, the following objectives had been formulated specific: a) To interpret more significant the ludopoiéticas experiences in the academic formation of graduandos of leisure; b) To analyze the experiences of the leisure most significant, disclosed for the group investigated, before, during and after the course; c) To describe and to interpret the process of autopoiese of the leisure and its respective meaning for the autoformação human being. The study it articulated the following metodológicas boardings: autobiogr á fica, etnogr á fica and fenomenológica. For the construction of the ludopoiéticas bridges between the academic formation proposal for the course of Leisure and Quality of Life of the CEFET-RN and the autoformação lived deeply human being as leisure for the participants of the study, we use as categories of analysis, five properties that had constituted the respective autopoiético system of the leisure. Thus, for our autopoiética reflectivity we adopt the following categories: autotelia; autoliberação; autoconectividade; autovalia and autofruição. The carried through research obtained to evidence given important of the ludopoié tica formation of these professionals of the leisure for its autoforma ç ã o human being and the autocriação of the proper leisure, that for recursividade feeds this autoformação in way permanently. Lived deeply properties of the ludopoiético system in the formation are searched with autonomy in the leisure. Thus, the learning of the autotelia, the autovalia, the autofruição and the autoconectividade lived deeply during the course of graduation in Leisure and Quality of Life is valued by the emotion of the joy and the love to the life, having become something desired by the citizens that had chosen the leisure as profession